DAMPAK PELARANGAN MUDIK AKIBAT PANDEMI COVID19 TERHADAP BISNIS ANGKUTAN UDARA DI INDONESIA - Dian Andaka (Journal of Civil Engineering and Planning (JCEP), 2020)
President Joko Widodo has issued a ban on all people to go home on Eid al-Fitr 1441 Hijri to suppress the spread of the covid19 virus. The purpose of this paper is to find out what the impact of the prohibition of going home due to the co-pandemic19 on the air transport business in Indonesia. One of the sectors affected by the prohibition of going home is the tourism sector. Another sector affected by air transport is the aviation itself. Various sectors, both formal and informal, experienced a very significant decrease in sales and impacted on rising unemployment in Indonesia. Also affects unemployment. Data collection techniques are using secondary data that is data obtained from previous researchers to be processed based on the author's personal thoughts. The results obtained from this study are a decrease in the number of passengers per February 2020 domestic flights by 10.06%, while international flights decreased by 31.25%. This certainly has the potential to go down further after the prohibition of going home. PT Garuda Indonesia (Persero) Tbk's total revenue. In Q1 2020, it decreased by 33%. In addition to the high season period, namely the Eid Mubarak, school holidays, and Hajj and Umrah this year, it is estimated that there will be no increase in the number of passengers. In March 2020 there was a decrease in hotel room occupancy by 20.64% of YoY. This decline figure is interpreted to continue to decline due to the prohibition of going home due to an increase in hotel occupancy rates in Lebaran and school holidays which in previous years could increase by up to 10%. Unemployment in DIY rose 0.52% to 3.38 % from the previous 2.86%. The potential increase in unemployment nationally can occur between 4.25 million people to 9.35 million people. The positive impact of the existence of this homecoming ban makes people not reduce the substance of going home during Eid al-Fitr that is mutual forgiveness via online to practice adaptation. Keywords : covid19, prohibition on return to hometown, air freight business